Development and stability of a nanostructured lipid carrier loaded with quercetin incorporated in a gel for transdermal use - Moraes, Jefferson Potiguara; Signori, Luis Ulisses; Rambo, Bianca; Mussoi, Thiago Durand; Laporta, Luciane Varini; Franco, Camila; Rech, Virginia Cielo (Disciplinarum Scientia | Naturais e Tecnológicas, 2022)
Quercetin is a flavonoid with antioxidant and anti-inflammatory potential. However, it has low skin permeation and stability. One way to improve this is to incorporate it into nanocarriers. This work aimed to develop and evaluate the stability of a nanostructured lipidic carrier with quercetin (NLC-Q) under different storage conditions for 30th days and its incorporation in the gel for 60th days. The NLC-Q were developed by the high shear rate method, and the physicochemical stability was performed at temperatures of 5, 25 and 40 oC on days 0, 7, 15, 22 and 30. The gel containing NLC-Q had its stability evaluated on days 1, 7, 15, 30, 45 and 60. The three environments’ size, polydispersity index (PdI), zeta potential (ZP), content (%), and pH are within the recommended parameters. Unlike the climatic chamber, where NLC-Q increased size, PdI and quercetin content (%) were reduced throughout the experiment. In the gel with NLC-Q, pH, viscosity, spreadability, size and PdI are within recommendations found in the literature. The NLC-Q kept at room temperature showed good stability throughout the study.